Formulation of refined, bleached and deodorised palm stearin with zinc dialkyl-dithiophosphate additive and its tribological performance - Azman, N. F. (Penerbit UTM Press, 2016)
Vegetable oils have recently received worldwide attention for their use as a lubricant base stock that has numerous advantages, including their environmental friendliness. In this study, a refined, bleached and deodorised palm stearin was selected as the base lubricant, and its friction and wear performance were investigated with a pin-on-disk tribotester. The effect of zinc dialkyl-dithiophosphate (ZDDP) additive in concentrations of 1wt%, 3wt% and 5wt% on friction and wear performance were evaluated. Commercial semi-synthetic oil SAE 15W50 was used for comparison purposes. The experiments were conducted at a sliding speed of 1.5 m/s under a normal force of 9.81 N for 60 min. Results show that an increase in ZDDP concentrations improved both friction reduction and wear performance of the lubricant. The coefficient of friction (COF) of RBD palm stearin was reduced approximately at 71% when 5wt% of ZDDP was added and it shows that the friction reduction performance of PS+5wt% (COF=0.039) was comparable to SAE 15W50 (COF=0.035). While, wear coefficient of RBD palm stearin was reduced significantly from 2.08 × 10−3 to 8.89 × 10−5 when 5wt% ZDDP additive was added and it shows that the wear performance of PS+5wt% was better than that of SAE 15W50, 1.94 × 10−4. Further analysis of the wear worn surface with a high-resolution optical microscope was also conducted with a surface profilometer to examine the metallurgy of the pin surface and the roughness of the pin.